CHẾ TẠO VÀ NGHIÊN CỨU TÍNH CHẤT, CẤU TRÚC CỦA VẬT LIỆU COMPOZIT TRÊN CƠ SỞ POLYETYLEN VÀ BÃ THẢI PHOTPHOGYP BIẾN TÍNH HỮU CƠ - Hoàng, Thái; Thẩm, Đỗ Quang; Giang, Nguyễn Vũ (Vietnam Journal of Chemistry, 2012)
This report dealed with using phosphogypsum (PG) waste as filler for high density polyethylene (HDPE) based composites. PG was modified by stearic acid and denoted as MPG. The composites of HDPE/MPG and HDPE/unmodified PG were prepared by melt mixing in a Haake Rheomixer. The presence of polyethylene grafted with acrylic acid (PEg) was used as a coupling agent for PG and HDPE. The obtained results showed that unmodified PG (UPG) strongly reduced mechanical properties of HDPE. But in comparison, the mechanical properties of HDPE/MPG were higher than those of HDPE/UPG composites with the same filler amount because MPG was more organophilic than UPG. The Haake torques indicated that both MPG and PEg increased melt viscosity of PE. PEg enhanced the dispersion and adhesion of MPG in PE matrix as expressed by SEM images. PEg also improved the mechanical properties of HDPE/MPG composites. The HDPE - based composites using both MPG and PEg exhibited higher thermal stability than neat HDPE. Keywords: phosphogypsum, HDPE-based composite, organophilic